A consolidated bioprocess design to produce multiple high-value platform chemicals from lignocellulosic biomass and its technoeconomic feasibility. (1st December 2022) - Maitra, Shraddha; Singh, Vijay
Abstract: 5-Hydroxymethyl furfural (HMF) and furfurals are DOE-listed platform chemicals that can be derived from the renewable carbon in the lignocellulosic biomasses and have the potential to replace petroleum-derived alternatives. High substrate cost and use of expensive solvents limit the economic feasibility of bio-based HMF production on an industrially relevant scale. The study presents an experimental optimized condition that maximizes the chemical-free production of HMF and furfurals without lowering the yield of total fermentable sugars from Saccharum bagasse. Hydrothermal pretreatment at 210 °C for 15 min yielded approximately 10%, 12%, and 46% of HMF, furfurals, and fermentable sugars per gram of dry biomass, respectively. Additionally, the study proposes a consolidated bioprocess model to produce and recover four high-value bioproducts i.e., HMF, furfurals, ethanol, and acetic acid based on the experimental results and evaluates its technoeconomic feasibility considering HMF as the main product. The minimum selling price (MSP) of HMF was estimated to be 930.6 USD/t which is competitive with its petroleum-derived precursor alternative p -xylene (1, 113 USD/t). The sensitivity analysis performed for the process parameters suggests that pretreatment cost and revenues from coproducts immensely influence the MSP of HMF. The preliminary technoeconomic analysis performed on the consolidated bioprocess design indicates that additional revenue streams from diversified coproducts in biorefineries aid in lowering the MSP of high-value bioproducts. Graphical abstract: Proposed bioprocess design to produce four diverse high-value bioproducts from Saccharum in a biorefinery. Image 1 Highlights: Advantageous dimension to the generation of inhibitors during biomass pretreatment. Optimizing generation of HMF, furfurals, acetic acid along with cellulosic sugars. Integrated bioprocessing model for four high-value bioproducts from Saccharum. Evaluation of technoeconomic feasibility of bioprocess and MSP of biobased HMF. MSP of HMF (930.58 USD/t) was competitive with its petroleum-derived alternative.